The effectiveness of entrepreneurship programmes and collaboration of institutions-industry in the technical and vocational training centres - Shuhod, Siti Fatimah; Mat Rashid, Abdullah (Human Resource Management Academic Research Society, 2023)
The entrepreneurship programme conducted at two technical and vocational training centres namely the mobile technical services (MTS) programme at MARA skills institute (IKM) and school enterprise (SE) in vocational colleges (KV) aims to produce more young entrepreneurs in the future. However, the rate of involvement of the younger generation in entrepreneurship and working in entrepreneurship is still decreasing and increases the unemployment rate among the youth. The design of the study is Ex Post Facto. This study aims to identify the effectiveness of entrepreneurship programmes and collaboration between institutions-industry in the MTS and SE programmes. Next, this study will determine whether there is a difference between the non-dependent variables i.e. institutional-industry collaboration in the MTS and SE programmes on the dependent variable which is the effectiveness of the entrepreneurship programme. Data was collected using questionnaire instruments involving 225 respondents through purposeful sampling method. Respondents were students of IKM under the Mechanical Department who conducted the MTS program as well as students who conducted the SE program at KV under the Mechanical Department in 2020 in the central zone (Kuala Lumpur and Selangor), the northern zone (Perlis) and the southern zone (Melaka). The questionnaire has 5 sections and is analyzed using descriptive and inferential statistical analysis, T-tests of non-dependent samples. The findings showed that the mean value of the MTS entrepreneurship program effectiveness variable was high (Min = 3.62, SP = .60) and the overall mean for the effectiveness of the SE entrepreneurship program was moderate (Min = 3.00, SP = .66). Min overall for the variable institutional collaboration with industry for the MTS entrepreneurship program recorded high value (Min = 3.64, SP = .63) and the SE entrepreneurship program was moderate (Min = 3.34, SP = .70).